Insight into the Structural Variation and Sodium Storage Behavior of Polyoxometalates Encapsulated within Single‐Walled Carbon Nanotubes. Issue 57 (22nd August 2022) - Sha, Quan; Cao, Dongwei; Wang, Jiaxin; Hu, Hanbin; Li, Jiaxin; Chen, Wei; He, Lei; Newton, Graham N.; Song, Yu‐Fei
Abstract: The host–guest interaction can remarkably alter the physiochemical properties of composite materials. It is crucial to clarify the mechanism by revealing the influence of the host on the electronic structure of the guest molecules. Herein, we study the structural variation of polyoxometalates (POMs) after being confined in single‐walled carbon nanotubes (SWNT). What we found is that in addition to the reported charge transfer from SWNT to POM, an intramolecular electron transfer within a single POM cluster can be observed in the POM@SWNT composites. Moreover, the charge density on the bridged oxygen of POMs is prominently enhanced. The structural change and electron reconfiguration of POMs upon encapsulation in SWNT significantly speed up electron and ion transport, leading to the improved electrochemical performance for sodium ions storage. Abstract : Confining polyoxometalates (POMs) in single‐walled carbon nanotubes (SWNTs) influence the electronic structure of POMs. Electron transfer occurs not only between POMs and SWNTs, but also within a single POM cluster. Consequently, charge density on the bridged oxygen of POMs is prominently enhanced. The electron reconfiguration of POMs in POMs@SWNT significantly accelerate electron and ion transport, and improve electrochemical Na + storage performance.